Implementasi Metode Computational Thinking Dan Implikasinya Terhadap Peningkatan Prestasi Siswa Mata Pelajaran Pendidikan Agama Islam - Amalia, Debby Rizki; Yanti, Anggi; Abdullah, Deba Muslim (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The decline in achievement in Islamic Religious Education subjects has become a problem as well as an evaluation material for PAI teachers and educational institutions in improving the quality of students. The purpose of this study was to determine the increase in student achievement in Islamic Religious Education subjects by implementing computational thinking. The formulation of the research problems are: 1) How is the Implementation of Computational Thinking Method? 2) How to Improve Student Achievement in Class X Multimedia at SMK Ciledug Al-Musaddadiyah Garut? 3) What are the implications of the Computational Thinking Method on Improving Student Achievement in Islamic Education Subjects? The research method used is a quasi-experimental with a mix method approach (mixed methods). Based on the results of research and qualitative and statistical data processing, there are results showing that the implementation of computational thinking in class X multimedia uses decomposition, pattern recognition, abstraction, and algorithms, the t value in the experimental group is 1.175 > the t table value is 0.692 so it can be concluded that computational thinking can improve student achievement in Islamic Religious Education subjects and there is a questionnaire score of 52% about students' perceptions that computational thinking is a fun learning method, compared to the discussion method obtained through questionnaire data of 48%.  Keywords: computational thinking, improvement of student achievement, Islamic religious education